Pengaruh Cita Rasa dan Persepsi Harga Terhadap Keputusan Pembelian Mie Ayam Yamin Gubeng Kertajaya Surabaya - Lisa Dwi; Ugy Soebiantoro (Jurnal Manajemen, 2022)
ABSCTRACT Currently, consumers tend to sort out processed foods and fast food drinks. One of the foods that are loved by the community is Chicken Noodles, because the presentation process does not require much time, has a distinctive taste, and affordable prices for all people. Although noodles are not from Indonesia chicken noodles have become a traditional Indonesian food. This dish has spread throughout Indonesia, especially the Java region, this dish is very easy to find. Not infrequently culinary cuisine bears the name of a region in Indonesia. The purpose of this study was to analyze the effect of taste and price perception on purchasing decisions of Yamin Gubeng Kertajaya Chicken Noodles in Surabaya. This study uses the Partial Least Square (PLS) method with a sample of 66 respondents. The results showed that taste and price perception had a positive and significant effect on purchasing decisions. Keywords : Taste, Price Perception, Purchase Decision